Crime and the penal policy of courts in the Hungarian people's republic (Archives of Criminology, 1987)
There is in Hungary a many years tradition. of gathering and publishing criminal statistics and its theoretical analysis. This tradition dates back to the early 19th century. In the modern days, it was discontinued in the years 1944-1956 only. However, in 1957, the publication of the basic data of criminal statistics in Statistical Yearbooks published by the central statistical Office was started anew.As shown by an analysis of the trends of the number of convictions of adults in the years 1944-1984 based on official sources, there is a high substantial changes in these trends with changes in the provisions of the penal law and to some extent in the socio-political climate. The following can thus be noticed:A very big number of convictions in the late fourties and early fifties (with the culminating point in 1952), accompanied by rapid drops in the years when amnesty laws were passed or new provisions of the penal law were introduced.A great drop in the number of convictions in 1956 and, 1957 which was related directly first of all to the course of events before and after October 23, 1956, and to the fact that a part of the jurisdiction of common courts of law was taken over by special courts of law was taken over by special courts the activity of which is not reflected in the analysed statistical data.A relative stabilization of the number of convictions in the years of gradual socio-political consolidation ( 1958-1962).A gradual increase in the number of convictions after the entering into force of the Penal Code of 1961 and its amendment of 1971. Accompanied by intermittent drops in the amnesty years and in the years when provisions that modified the Penal Code entered into force.An increase in the number of convictions after the entering into force of the Penal Code of 1978.The rate of convictions per 100,000 of the population in 1984 was 2'5 times higher than in 1952, but not much lower than the 1961 rate.The rise in crime in the recent years is also evident in the available data from the police and public prosecutor's statistics. The number of reported offences went up by one-third in the period 1965-1985 and has a constant upward trend.Among the offences reported most numerous are offences against property (about 60 per cent of all reported offences), traffic offences (about 12-13 per cent), offences against public order (hooliganism and parasitism in particular), and offences against person (about 7-8 per cent). As compared with 1965, the number of burglaries was 3.5 times as big in the eighties, and the number of robberies - 7 . times. The number of traffic offences increased by over one-third as well. Also offences against person reveal a small upward trend, with the number of homicides being stable. However, the number of homicides in Hungary has for many years been considerably larger than the mean European figure (mean homicide rate per 100,000 of the population amounting to 3.8 in the years 1979--1983). The rise in crime concerned financial offences also (offences against the foreign currency exchange regulations, against customs regulations, tax offences) which are included in ,the group of offences against the national economy.The penal policy of the Hungarian courts has rather frequently been subject to spectacular transformations. In the early seventies, stabilization was achieved in this policy which manifested itself by a limited application of unconditional deprivation of liberty and by a broad use of fine and other measures not involving deprivation of liberty. However, the rise in crime in the eighties influenced a more frequent application of unconditional deprivation of liberty, which resulted in the growth of prison population. In 1979, the number of persons deprived of liberty amounted to 16,764 (157 per 100,000 of the population), while in 1984 the respective number was 21,884 (205 per 100.000 of the population).In Hungary, conditional suspension of the execution of the penalty of deprivation- of liberty is not as popular as in other European socialist countries. For every fifth convicted person, the execution of penalty is suspended.In 1973, the courts for the- first time passed a greater number of fines (48.8 per cent) than prison sentences (43.9 per cent). In the-following years, the share of fines in the structure of penalties even exceeded 50 per cent. However, after entering into force of the new Penal code, an unexpected drop in the number of fines took place things to the which was due among other fact that some of the  petty offences were removed from the Penal Code , and that a new penal measure without deprivation of liberty, i.e. probation, was introduced. In 1983, the share of fines dropped to 40 per cent of all sentences.The Hungarian courts were most reluctant to apply the penalty of corrective and educational work as soon as the penalty was introduced in 1950. For a dozen-odd years the share of this penalty in all penalties imposed never exceeded 10 per cent. After the 1961 Penal Code was introduced the penalty of corrective and educational work  showed an upward trend (up to 15,8 per cent in 1964), but later on started to fall up, to 4 per cent in 1983.In the years 1962 -1983. common courts sentenced 105 persons to death penalty, for qualified homicide in the vast majority of cases. Since 1968, this penalty has been applied exlusively towards the perpetrators of homicide.In 1984, the extent of reported crime in Hungary was similar to that found in Poland (1, 470 per 100,000 o0f the population); however, in Hungary the response to the rise in crime has been in general much more balanced and quiet.